Human Metapneumovirus: Mechanisms and Molecular Targets Used by the Virus to Avoid the Immune System - Soto, Jorge A.; Gálvez, Nicolás M. S.; Benavente, Felipe M.; Pizarro-Ortega, Magdalena S.; Lay, Margarita K.; Riedel, Claudia; Bueno, Susan M.; Gonzalez, Pablo A.; Kalergis, Alexis M. (Frontiers in Immunology, 2018)
Human metapneumovirus (hMPV) is a respiratory virus, first reported the year 2001. Since then, it has been described as one of the main etiological agents that causes acute lower respiratory tract infections (ALRTIs), which is characterized by symptoms such as bronchiolitis, wheezing and coughing. Susceptible population to hMPV-infection includes newborn, children, elderly and immunocompromised individuals. This viral agent is a negative-sense, single-stranded RNA enveloped virus, that belongs to the Pneumoviridae family and Metapneumovirus genus. Early reports—previous to 2001—state several cases of respiratory illness without clear identification of the responsible pathogen, which could be related to hMPV. Despite the similarities of hMPV with several other viruses, such as the human respiratory syncytial virus or influenza virus, mechanisms used by hMPV to avoid the host immune system are still unclear. In fact, evidence indicates that hMPV induces a poor innate immune response, thereby affecting the adaptive immunity. Among these mechanisms, is the promotion of an anergic state in T cells, instead of an effective polarization or activation, which could be induced by low levels of cytokine secretion. Further, the evidences support the notion that hMPV interferes with several pattern recognition receptors (PRRs) and cell signaling pathways triggered by interferon-associated genes. However, these mechanisms reported in hMPV are not like the ones reported for hRSV, as the latter has two non-structural proteins that are able to inhibit these pathways. Several reports suggest that viral glycoproteins, such as G and SH, could play immune-modulator roles during infection. In this work, we discuss the state of the art regarding the mechanisms that underlie the poor immunity elicited by hMPV. Importantly, these mechanisms will be compared with those elicited by other common respiratory viruses.